Abid Al-Jabiri’s Epistemological Critique of Early Marriage in Case Based Learning: Contributions to Islamic Education - Muniri Muniri; Anis Sulalah; Nur Chotimah Azis (STAI Hubbulwathan Duri, 2025)
Early marriage remains a pressing issue in many Muslim communities, including in Bangkalan, Madura, Indonesia, where it is often justified through religious reasoning. This phenomenon poses serious social, health, and educational challenges, particularly for young women. This study aims to critically examine early marriage through the lens of Abid Al-Jabiri’s Islamic epistemology—Bayani, Burhani, and Irfani—and to explore how these epistemological frameworks shape religious understanding and educational responses to early marriage. Utilizing a qualitative library research approach, this study analyzes relevant literature, including Islamic texts, philosophical works, and empirical research on early marriage. The analysis applies Al-Jabiri’s epistemological framework to assess the reasoning patterns behind the justification of early marriage and their impact on educational practices. The study finds that Bayani (textual) and Irfani (mystical) epistemologies often perpetuate early marriage due to their non-empirical and authority-based approach. In contrast, Burhani (rational-empirical) epistemology, which emphasizes logical reasoning and empirical evidence, offers a more critical and socially responsive framework. When applied to educational contexts, Burhani epistemology supports a more reflective, contextual, and student-centered understanding of Islamic teachings. Integrating Burhani epistemology into Islamic education and policy discourse can foster a more balanced, evidence-based approach to religious interpretation. This shift is essential to counter harmful practices such as early marriage and to promote holistic well-being and critical thinking among students in Islamic educational settings.